The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.cbpc.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Growth, toxin production, active oxygen species and catalase activity of Microcystis aeruginosa (Cyanophyceae) exposed to temperature stress

Abstract: Microcystis are known for their potential ability to synthesize toxins, mainly microcystins (MCs). In order to evaluate the effects of temperature on chlorophyll a (Chl a), growth, physiological responses and toxin production of a native Microcystis aeruginosa, we exposed the cells to low (23°C) and high (29°C) temperature in addition to a 26°C control treatment. Exponential growth rate was significantly higher at 29°C compared to 23°C and control, reaching 0.43, 0.32 and 0.33 day −1 respectively. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 64 publications
8
31
1
Order By: Relevance
“…The production of [D-Leu 1 ] MC-LR decreased with increasing temperature, coinciding with the findings of Gorham, 1964;Runnegar et al, 1983;van der Westhuizen and Eloff, 1985;Cood and Poon, 1988;Sivonen, 1990;Rapala et al, 1997;Lehman et al, 2008;Wang et al, 2010 andGiannuzzi et al (2016). van der Westhuizen and Eloff (1985) reported that the optimal growth conditions do not coincide with the production of toxins.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The production of [D-Leu 1 ] MC-LR decreased with increasing temperature, coinciding with the findings of Gorham, 1964;Runnegar et al, 1983;van der Westhuizen and Eloff, 1985;Cood and Poon, 1988;Sivonen, 1990;Rapala et al, 1997;Lehman et al, 2008;Wang et al, 2010 andGiannuzzi et al (2016). van der Westhuizen and Eloff (1985) reported that the optimal growth conditions do not coincide with the production of toxins.…”
Section: Discussionsupporting
confidence: 68%
“…The supernatant was passed through conditioned (10 mL 100% methanol, 50 mL 100% distilled water) Sep-Pak C18 cartridges (Waters) and the MCs were eluted with 80% methanol (Barco et al, 2005). Quantitative chromatographic analysis of MCs was performed by HPLC/MS Shimadzu LCMS-2020 determining a principal component of [D-Leu 1 ] MC-LR toxins (m/z 520) using C18 column (Hyperprep HS, 5-mm pore, 250 mm 10 mm) according to Giannuzzi et al (2016) …”
Section: Total MC Quantificationmentioning
confidence: 99%
“…Crettaz Minaglia [39] found that the production of MC-LR decreased with increasing temperature, coinciding with the findings of [43][44][45][46][47][48][49][50].…”
Section: Introductionsupporting
confidence: 68%
“…While high enough concentrations of H 2 O 2 efficiently kill cyanobacteria, sub-lethal concentrations of H 2 O 2 may rapidly initiate antioxidant defenses in cyanobacteria. Such defense mechanisms may enhance at least the production of MC-LR (Giannuzzi et al 2016). It has also been reported the binding of MC to proteins increases the fitness of Microcystis under oxidative stress (Zilliges et al 2011).…”
Section: Use Of H 2 O 2 For Elimination Of Cyanobacteria and Mcsmentioning
confidence: 92%